Noise exposure assessment during movie screenings at a movie theatre in Kuantan - Ishak, Juliahana; Mohammed Fauzi, Luqman Al-Bashir; Razali, Ailin (IIUM Press, International Islamic University Malaysia, 2017)
The number of people with noise-induced hearing loss (NIHL) in Malaysia is increasing. However, there is no information on whether leisure activities premises are exposing the public to the risk of NIHL. This book, consisting of two parts, assessed the noise exposure during the screenings of movies at a selected movie theatre. The first part of the book measured the noise levels during the screening of 18 movies. For each movie, two readings were taken, one from a center seat and one from a side seat. The genre of the movies and the size of the theatre halls were taken into consideration in the analysis. The second part focussed on determining any statistically significant difference of the seat locations on the equivalent continuous sound level (Leq) and maximum sound level (LASMX) in the same theatre hall showing the same movie.